1979
DOI: 10.1099/00221287-114-2-305
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Surface Protein Composition Associated with Virulence Properties in Opacity Types of Neisseria gonorrhoeae

Abstract: 305The biological properties of a series of opacity variants of Neisseria gonorrhoeae P9 have been examined. A novel protein, designated protein IId* (mol. wt 28850), was identified within the set of heat-modifiable surface proteins previously reported. All variants producing extra outer membrane proteins were less sensitive to the bactericidal action of serum than the prototype transparent strain, with protein Ira* (mol. wt 28 500) being associated with increased resistance. The production of a different prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
140
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(142 citation statements)
references
References 7 publications
2
140
0
Order By: Relevance
“…Neisseria gonorrhoeae P9 variants were grown on clear typing medium as previously described (Lambden et al, 1979). Colonies of P9-2 (u pili) and P9-20 Vpili) (Lambden et al, 1980) were picked, purified by repeated single colony isolation and stored in liquid nitrogen.…”
Section: E T H O D Smentioning
confidence: 99%
“…Neisseria gonorrhoeae P9 variants were grown on clear typing medium as previously described (Lambden et al, 1979). Colonies of P9-2 (u pili) and P9-20 Vpili) (Lambden et al, 1980) were picked, purified by repeated single colony isolation and stored in liquid nitrogen.…”
Section: E T H O D Smentioning
confidence: 99%
“…Rather, it must reflect either the preferred expression or the enhanced survival of variants that express a protein II other than PIIa. Relatively little is known about either the comparative survival abilities of different PII variants in vitro (12) or their differential expression of their P.II repertoire. Although all protein II genes are switched on-off by gain or loss of pentameric repeats in its leader peptide-encoding portion (26,27), different P.II genes switch on-off at very different frequencies among cells in a given strain (19, 32, Swanson, J ., unpublished results) .…”
mentioning
confidence: 99%
“…Protein II' in vitro exhibit striking aggregation, and this might enhance colonization in vivo if it promotes the retention of newly multiplied organisms at infected mucosal loci . In addition, several studies have demonstrated heightened attachment of protein II+ gonococci to eukaryotic cells in vitro (12)(13)(14)(15). One report suggests that, after their attachment to HeLa cells, some P.II+ variants are detached more readily than others (15) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gonococci expressing PII proteins are generally isolated from infections localized to the surface mucosa, whereas organisms recovered from disseminated infections often lack PII proteins (6,7). The possession of certain PII proteins has been associated with resistance to antibiotics and steroid hormones (12,19), altered-serum resistance (8,12), increased sensitivity to serum proteases (2), and increased adherence to buccal epithelial cells (12) and phagocytic cells (18).…”
mentioning
confidence: 99%